Relationships between Hoffa fragment size and surgical approach selection: a cadaveric study - Wich Orapiriyakul (2018)
© 2018, Springer-Verlag GmbH Germany, part of Springer Nature. Introduction: Fixation of a small Hoffa fragment requires a selection of the proper surgical approach for reduction and posterior to anterior screws fixation. However, currently there are no guidelines regarding how to select the best approach for small posterior Hoffa fractures. Objectives: To compare the size of Hoffa fractures that are appropriate for reduction and fixation with the medial parapatellar approach (MPPA) and those which require the direct medial approach (DMA), and to make a similar comparison between the lateral parapatellar approach (LPPA) and the posterolateral approach (PLA). Materials and methods: Twenty extremities of fresh cadavers were included. After completion of each approach, the articular surface boundaries were marked and soft tissue was removed. On the medial condyle, an imaginary line was drawn from the most anterior (A) to the most posterior (B) point, representing the AP diameter (d3). The most posterior boundary of MPPA (C) and the most anterior boundary of DMA (D) were similarly marked. Distances between B and C (d1) and between B and D (d2) were measured as well as the anterior–posterior diameter of the condyle (d3). The same measurements were made for the lateral condyle. Results: On the medial condyle, the average values of d1, d2, and d3were 10.8 mm ± 3.8, 17.3 mm ± 3.3, and 60.1 mm ± 3.2, while percentages of d1/d3and d2/d3were 18.3% ± 6.4 and 28.7% ± 4.7. In lateral condyle, the averages for d1, d2, d3were 6.1 mm ± 1.4, 12.1 mm ± 2.8 and 60.9 mm ± 3.3 mm and the percentages of d1/d3and d2/d3were 10.1% ± 2.3 and 19.9% ± 4.9. Conclusions: When the Hoffa fragment is less than 18.3% of the AP diameter of medial condyle or 10.1% of lateral condyle, the fracture is invisible with the PPA. When the Hoffa fragment is more than 28.7% of the medial condyle or 19.9% of the lateral condyle, the PPA should be selected. If the Hoffa fragment is less than 28.7% of the medial condyle or 19.9% of the lateral condyle, the DMA or PLA with posterior-to-anterior screws is recommended. Combined approaches should be considered in some complex cases with articular comminution.